18) Differentiate (2x + 5) (3x + 7)-1 by using product rule, and quotient rule respectively. Verify that the answers obtained are the same.

PRODUCT RULE :Let y = 2x+53x+7-1dydx = 2x+5×ddx3x+7-1 + 3x+7-1×ddx2x+5dydx = 2x+5×-33x+72 + 13x+7×2dydx = -32x+53x+72 + 23x+7dydx =-32x+5 + 23x+73x+72dydx = -6x - 15 + 6x + 143x+72dydx = -13x+72QUOTIENT RULE :Let y = 2x+53x+7-1y = 2x + 53x + 7dydx = 3x+7×ddx2x+5 - 2x+5×ddx3x+73x+72dydx = 3x+7×2 - 2x + 5×33x+72dydx = 6x + 14 - 6x - 153x+72dydx = -13x+72

  • 1
What are you looking for?